2020
DOI: 10.1101/2020.03.09.20033381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Coronavirus (COVID-19) Knowledge and Perceptions: A Survey of Healthcare Workers

Abstract: Background: During the first week of March, the surge of coronavirus disease 2019 cases reached over 100 countries with more than 100,000 cases. Healthcare authorities have already initiated awareness and preparedness activities beyond borders. A poor understanding of the disease among healthcare workers (HCWs) may result in delayed treatment and the rapid spread of infection. This study aimed to investigate the knowledge and perceptions of HCWs about COVID-19. Methods:A cross-sectional, web-based study was c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

63
245
12
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(329 citation statements)
references
References 12 publications
63
245
12
9
Order By: Relevance
“…Findings are consistent with number of studies as Giao et al reported social media as a main source of information regarding COVID-19 used by 91.1% participant health care workers [22]. Similarly, a study conducted among 453 HCPs found that more than 60% respondents use social media to seek information regarding COVID-19 [10]. This is important as in this global pandemic, there is also a pandemic of misinformation regarding COVID-19; a serious concern might lead to xenophobia in the world as already warned by scientists and WHO officials [23] [24].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Findings are consistent with number of studies as Giao et al reported social media as a main source of information regarding COVID-19 used by 91.1% participant health care workers [22]. Similarly, a study conducted among 453 HCPs found that more than 60% respondents use social media to seek information regarding COVID-19 [10]. This is important as in this global pandemic, there is also a pandemic of misinformation regarding COVID-19; a serious concern might lead to xenophobia in the world as already warned by scientists and WHO officials [23] [24].…”
Section: Discussionsupporting
confidence: 89%
“…Also, there is plethora of malicious and unverified information waved on internet that spread quickly and could misguide the HCPs. So, situation demands that HCPs should carefully evaluate COVID-19 information sources and utilize authentic and valid content to seek information [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On 31 December 2019 first case of new of pneumonia of corona virus was registered in Wuhan, Hubei province in China now known as the COVID-19 which is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2), symptoms include cough, fever and shortness of breath (1)(2)(3). Virus is a kind of zoonotic pathogens that is able to be transmitted through both animal and human contacts (3,5). On 11 March 2020 the World Health Organization (WHO) declared the COVID-19 as a global pandemic, since then COVID-19 cases has been increasing rapidly up to 697,244 confirmed cases, 33,257 deaths in over more than 204 countries as at 31 March (4).…”
Section: Introductionmentioning
confidence: 99%